Time-Related Alteration in Flow- (Shear Stress-) Mediated Remodeling in Resistance Arteries from Spontaneously Hypertensive Rats - Odile Dumont; Gilles Kauffenstein; Anne-Laure Guihot; Nathalie C. Guérineau; Pierre Abraham; Laurent Loufrani; Daniel Henrion (International Journal of Hypertension)
Hypertension is a major risk factor for cardiovascular disorders. As flow-mediated outward remodeling has a key role in postischemic revascularization, we investigated this remodeling in mesenteric resistance arteries of normotensive (WKY) and spontaneously hypertensive rats (SHRs) aged 3 to 9 months. Sequential ligation of mesenteric resistance arteries allowed modifying blood flow in vivo, thus exposing arteries to low, normal, or high flow. After 1, 3, 8, or 24 weeks, arteries were isolated for in vitro study. High flow (HF) induced outward hypertrophic remodeling in WKY rats after 1 week and persisted until 24 weeks without change in wall to lumen ratio. In SHRs, diameter increase was delayed, occurring only after 3 weeks. Nevertheless, it was reduced at 8 weeks and no longer significant after 24 weeks. In parallel, media cross-section area increased more with time in SHRs than in WKY rats and this was associated with increased contractility and oxidative stress with decreased NO-dependent relaxation. Low flow induced progressive inward remodeling until 24 weeks in both strains with excessive hypertrophy in SHRs. Thus, a chronic increase in flow induced transitory diameter expansion and long-lasting hypertrophy in SHRs. This could contribute to the higher susceptibility of hypertensive subjects to ischemic diseases.